Role of HRM to Support Line Managers for Successful Service Management - Nayal, Rupesh (Journal of Advanced Research in Service Management, 2022)
According to the research, effective human resource management practices are a crucial component of the success of every contemporary organization. A large number of academics have discussed the significance of having efficient HRM practices in order to sustain and survive. However, the HRM department need to operate and control each and every person in the organization. Where do managers fit in the overall role of the organization? How can the HRM department support those managers in the day-to-day operations of operating and managing their employees? The purpose of this study is to investigate and define the role that an HRM department plays in providing support to line managers in an organization to achieve successful service management for their organization. The historical approach will be used as the technique for this work, and the literature review will serve as the instrument. The primary results were as follows: there are many things that the HRM department of the company can do to improve and support the roles of line managers; there are specific capabilities that the HRM department ought to have in order to qualify HRM staff to play the supporting role to line managers. Because of this, HRM staff should be picked effectively in order to help an organization in meeting its objectives and continuing to sustain and survive.